Additive Manufacturing of Fiber-Reinforced Polymers: A Route to Sustainable and Advanced Manufacturing - Madhu Puttegowda; Sanjay Mavinkere Rangappa; Suchart Siengchin (Journal of Fibers and Polymer Composites, 2026)
Editor's Corner